2018
DOI: 10.1186/s12885-018-4640-y
|View full text |Cite
|
Sign up to set email alerts
|

Bulk tumour cell migration in lung carcinomas might be more common than epithelial-mesenchymal transition and be differently regulated

Abstract: BackgroundEpithelial-to-mesenchymal transition (EMT) is one mechanism of carcinoma migration, while complex tumour migration or bulk migration is another - best demontrated by tumour cells invading blood vessels.MethodsThirty cases of non-small cell lung carcinomas were used for identifying genes responsible for bulk cell migration, 232 squamous cell and adenocarcinomas to identify bulk migration rates. Genes expressed differently in the primary tumour and in the invasion front were regarded as relevant in mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 48 publications
1
26
0
2
Order By: Relevance
“…EpCAM+, Cytokeratins+, E-cad+, Vimentin+, N-cad+, O-cad+, CD133+ [85] CTCs from women with metastatic BT Hybrid EMT Cytokeratins+, Vimentin+, N-cad+ [85] ESCC PT or MLN specimen from ESCC patients E-cad+, N-cad+, vimentin+ [86] CTC from early stage breast cancer patients stemness TWIST1+, CD44+, ALDH1+, EpCAM+ [87] Breast cancer samples from primary site and metastatic lymph nodes of breast cancer patients Co-expression of E/M markers E-cad+, vimentin+ [88] Human primary colorectal cancer specimen Cytokeratin+, vimentin+ [89] Primary HGSOC tumour E-cad+, vimentin+ [90] Primary AC, SCC tumours Vimentin+/cytokeratin+, E-cad+/N-cad+ [91] Abbreviations: ANKRD1, ankyrin repeat domain-containing protein 1; AOX1, aldehyde oxidase 1; COL3A1, collagen Type III α1 Chain; FGF2, fibroblast growth factor; LAMC2, laminin subunit γ 2; MME, membrane metallo-endopeptidase.…”
Section: Clinical Evidence Of Partial Emt In Human Cancersmentioning
confidence: 99%
“…EpCAM+, Cytokeratins+, E-cad+, Vimentin+, N-cad+, O-cad+, CD133+ [85] CTCs from women with metastatic BT Hybrid EMT Cytokeratins+, Vimentin+, N-cad+ [85] ESCC PT or MLN specimen from ESCC patients E-cad+, N-cad+, vimentin+ [86] CTC from early stage breast cancer patients stemness TWIST1+, CD44+, ALDH1+, EpCAM+ [87] Breast cancer samples from primary site and metastatic lymph nodes of breast cancer patients Co-expression of E/M markers E-cad+, vimentin+ [88] Human primary colorectal cancer specimen Cytokeratin+, vimentin+ [89] Primary HGSOC tumour E-cad+, vimentin+ [90] Primary AC, SCC tumours Vimentin+/cytokeratin+, E-cad+/N-cad+ [91] Abbreviations: ANKRD1, ankyrin repeat domain-containing protein 1; AOX1, aldehyde oxidase 1; COL3A1, collagen Type III α1 Chain; FGF2, fibroblast growth factor; LAMC2, laminin subunit γ 2; MME, membrane metallo-endopeptidase.…”
Section: Clinical Evidence Of Partial Emt In Human Cancersmentioning
confidence: 99%
“…Mild increase in hepatocytic mitosis (orange arrow) was observed in the liver of mice treated with free drugs. The abnormal histological symptoms detected (white arrow) in the lung and liver of mice treated with saline and empty Na-DOC-hyd+G4.5 biomaterial indicated the possibility of metastasis in mice not treated with any therapeutic drugs [ 65 , 66 ]. In contrast, organs collected specifically from mice treated with the Na-DOC-hyd-RESV+G4.5-DOX formulation did not show any significant histological abnormality, confirming the biosafety of the drug carriers, as well as RESV.…”
Section: Resultsmentioning
confidence: 99%
“…Our study might suggest that, although emt is one of the most important causes of tumour metastasis, other factors could play crucial role in lung adenocarcinoma. Bulk tumour-cell migration has been reported to potentially be more common than emt in lung carcinoma, and tumour cells were found to be able to migrate without changing to the mesenchymal phenotype called "epithelial migration type" 36 . Some studies have shown that reduction in E-cadherin expression is related to a decrease in sensitivity to epidermal growth factor receptor tyrosine kinase inhibitor and to EGFR status 37,38 , results that are not consistent with the present study.…”
Section: Discussionmentioning
confidence: 99%